Pengaruh Penambahan Ekstrak Buah Duwet dan Bunga Mawar pada Kemasan Pintar Berbasis Selulosa Bakteri sebagai Indikator Kerusakan Makanan - Winata, Kezia Jasmine; Anggara, Jaclyn Regina; Angkadjaja, Belinda Manuela; Gunawan, Fayola Feivel; Sulistyo, Joko (Abdimas Indonesian Journal, 2024)
Despite its environmental and health drawbacks, plastic continues to be widely used because of its cost-effectiveness and versatility. This study investigates the potential of biodegradable plastic made from cellulose derived from nata de coco, which is produced through the fermentation of Acetobacter xylinum bacteria, as a sustainable alternative to conventional non-biodegradable plastics. The structural integrity of the bioplastic was improved by adding cassava starch, glycerin, and CMC. Additionally, extracts from rose and Java plum were incorporated into the material to serve as indicators of food spoilage. Functionality tests revealed that the bioplastic containing rose extract demonstrated the most significant color change, likely due to the degradation of anthocyanins present in the extract. This research presents a promising approach to addressing plastic pollution and reducing food waste through the use of biodegradable smart packaging.